Corporate social responsibility in online retail – Perceptions from online discussions on Amazon - Heikkonen, Jussi (My University, 2016)
Online retail has experienced substantial growth due to the increased utilization of digital technologies. The growth in the industry has created numerous multinational corporations, which serve customers all around the world. As a result, the online retailers’ efforts in sustainability have been more often in publicity. Corporate Social Responsibility (CSR), the efforts going beyond the company’s interest in order to bring social good, have been discussed in the academic community for decades. While the various effects of CSR in retail and business generally have been realized, the research aims to make a contribution by examining the concept from the viewpoint of online retail by focusing on interaction at online discussion forums. The main research question asks: What is the role of online retailer CSR in the online discussion forum context? In order to answer this question, additional three sub-research questions are suggested: 1) What elements of CSR are relevant in the online retailer context? 2) How are discussion forums used in communication regarding CSR and online retail by different discusser types? 3) What kind of company perceptions and consumer behavior appear in online discussions of Amazon’s CSR? The study is qualitative of nature, using the content analysis research method to examine posts found from four different public online discussion forums. A qualitative, interpretative analysis was used, although quantitative measures regarding discussion posts were also presented. The analysis contains a coding process, where attributes are attached to discussion posts. As a result of the process, specific patterns can be indicated in order to categorize the posts. As the research uses Amazon as the case company, the case study method is also adopted. In the online retail context, ethics regarding the online retailer’s tax and labor policies are found as most relevant elements. Customers, using discussion forums to share their experiences and opinions regarding online retailer CSR efforts, are realized as the most prominent stakeholder. The research also highlights the role of online retailer employees providing details on internal business practices. However, the not realize the possibility to participate in discussions. Most discussion posts refer either to a positive, negative or mixed reaction towards CSR efforts, it is suggested that the concept is relevant also in online retail. Although online retailer CSR efforts are somewhat linked to company perceptions, the concept has a minimal role in consumer behavior. In online retail, CSR efforts can reduce the risk of being involved in discussions related to controversies. In addition, online retailer CSR efforts should communicate how the retailer contributes locally.